Outcome of Burkholderia (Pseudomonas) cepacia colonisation in children with cystic fibrosis following a hospital outbreak. - Whiteford, M. L. (1995)
BACKGROUND--While there are reports on the outcome in adults and teenagers with cystic fibrosis of colonisation with Burkholderia (Pseudomonas) cepacia, there is little information in children. METHODS--In December 1991 only one of 115 children with cystic fibrosis attending a paediatric centre was colonised with B cepacia. Over the next 12 months there was a rapid increase with 23 (20%) becoming colonised; eighteen (79%) of these became colonised in hospital at a time that overlapped with the admission of a B cepacia positive child. Three different bacteriocin types were isolated, with one type (S22/PO) being present in 17 (74%) patients. The outcome for children who became colonised with B cepacia was compared with that in 33 children who continued to be colonised with Pseudomonas aeruginosa alone. RESULTS--Children colonised with B cepacia were older and more poorly nourished than those colonised with P aeruginosa, but did not have poorer pulmonary function. After colonisation, the forced expiratory volume in one second (FEV1) deteriorated between consecutive annual tests, with the average deterioration being greater in those with higher initial levels. Five children with B cepacia died from respiratory failure although none showed a fulminant deterioration. Introduction of segregation measures within hospital led to a dramatic decrease in the number of newly colonised patients. CONCLUSIONS--This study provides further evidence for person-to-person spread of B cepacia and confirms the effectiveness of simple isolation measures in interrupting spread. Colonisation with B cepacia and P aeruginosa in children is associated with a more rapid decline in lung function and a significantly increased mortality compared with cases colonised with P aeruginosa alone.